If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8f + -4 = 6f + 26 Reorder the terms: -4 + 8f = 6f + 26 Reorder the terms: -4 + 8f = 26 + 6f Solving -4 + 8f = 26 + 6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6f' to each side of the equation. -4 + 8f + -6f = 26 + 6f + -6f Combine like terms: 8f + -6f = 2f -4 + 2f = 26 + 6f + -6f Combine like terms: 6f + -6f = 0 -4 + 2f = 26 + 0 -4 + 2f = 26 Add '4' to each side of the equation. -4 + 4 + 2f = 26 + 4 Combine like terms: -4 + 4 = 0 0 + 2f = 26 + 4 2f = 26 + 4 Combine like terms: 26 + 4 = 30 2f = 30 Divide each side by '2'. f = 15 Simplifying f = 15
| 3y/x | | 3a+4b=(1-2c)/d | | (x/3)-4=5 | | 1/5x=10-5 | | 5(3+x)+1=71 | | 175.000+550.00-1.00x=220.650 | | -5+6x+4x^2+x^3=0 | | 3z+6=17 | | 0.5x+11=17 | | 9(x-5)=x+22(1/2) | | k/5+5=7 | | (-3/5)x=15 | | x-27=19 | | 4x^2+x^3=0 | | 4p^2-11p-3=0 | | 6x+4x^2=0 | | 0.5=2(0.7)x+x^2 | | -1/2(5) | | 8x^5-64x^3=0 | | 7x+5y+10=0 | | x+13 | | 4*4-2=y+4 | | (2s)+(7s-18)=90 | | 9x+27=(9x+2)+9 | | x^3+4x^2+6x-5=0 | | 8x^4+16x^3+125x+250=0 | | 1/4+1/8*1/9 | | 15-3j=15 | | 2x1/3 | | 9.99+1.25*11= | | -2.7x^2+30x+6.5= | | 6t+3s+4c+4t+2s+3c= |